Immunohistochemical and molecular genetics study of a granular cell astrocytoma: A case report of malignant transformation to a glioblastoma. Issue 3 (21st September 2012) - Ishii, Taiji; Mizukawa, Katsu; Sasayama, Takashi; Sasaki, Hikaru; Hayashi, Saeko; Nakamizo, Satoshi; Tanaka, Hirotomo; Tanaka, Kazuhiro; Hara, Shigeo; Hirai, Chihoko; Itoh, Tomoo; Kohmura, Eiji
<x xml:space="preserve">Abstract</x> We treated a 56‐year‐old woman who had a right temporal lobe tumor found by chance after a traffic accident. MRI confirmed a heterogeneously enhanced tumor in the temporal lobe with large peritumoral edema extending to the superior parietal lobe. The patient underwent tumor resection. The tumor consisted largely of distinct cells with discrete borders and granular cytoplasm. In granular cells, the accumulation of PAS‐positive granules was observed. Immunohistochemical analysis demonstrated positive staining for GFAP, S‐100, and oligodendrocyte transcription factor 2 and negative staining for synaptophysin. CD68 was negative in granular cells, but positive in stromal cells. Ki‐67 labeling index was quite low. The tumor was diagnosed as a granular cell astrocytoma (GCA). Postoperative radiotherapy combined with temozolomide was administered. One month after chemoradiotherapy, the tumor occurred in the parietal lobe, and a tumorectomy was performed. The tumor was composed of poorly differentiated astrocytic tumor cells with prominent microvascular proliferation and necrosis. A small number of granular cells were locally observed and the tumor was diagnosed as a glioblastoma. O6‐methylguanine–DNA methyltransferase promoter methylation was detected in the GCA but not in the glioblastoma. Isocitrate dehydrogenase mutations were not detected in either tumor. Comparative genomic hybridization analysis demonstrated that no chromosomal abnormality was found in the GCA; however, a gain of chromosomes 7 and 19 and a loss of chromosomes 10 and 9p21 (CDKN2A) were found in the glioblastoma. p53 was strongly expressed in both the GCA and glioblastoma. The tumor progressed despite extensive chemotherapy, and the patient died 1 year after the initial treatment. Our immunohistochemical, genetic and chromosomal analyses indicate that the glioblastoma was transformed from the GCA.